The Combined Effect of Four Nutraceutical-Based Feed Additives on the Rumen Microbiome, Methane Gas Emission, Volatile Fatty Acids, and Dry Matter Disappearance Using an In Vitro Batch Culture Technique - Kelechi A. Ike; Deborah O. Okedoyin; Joel O. Alabi; Oludotun O. Adelusi; Michael Wuaku; Lydia K. Olagunju; Chika C. Anotaenwere; DeAndrea Gray; Peter A. Dele; Ahmed E. Kholif; Misty D. Thomas; Uchenna Y. Anele (Fermentation)
This study aimed to investigate the effect of an essential oil/fumaric combination, mannan-oligosaccharide, galactooligosaccharide, and a mannan-oligosaccharide/galactooligosaccharide combination on the dry matter disappearance (DMD), gas production, greenhouse gasses, volatile fatty acid, and microbial community of a total mixed ration using a 24 h in vitro batch culture technique. The study design was a completely randomized design with four treatments as follows: a control treatment without any additives, the control treatment supplemented with galactooligosaccharide at 3% (Gos treatment), a galactooligosaccharide and mannan-oligosaccharide mixture at 1:1 at 3% (Gosmos treatment), or an essential oil blend (200 μL/g feed) and fumaric acid at 3% combination (Eofumaric treatment). The Gosmos treatment had the highest (p < 0.05) DMD (63.8%) and the numerical lowest acetate–propionate ratio (p = 0.207), which was 36.9% higher compared to the control. The lowest Shannon index, Simpson’s index, and all the diversity indices were recorded for the Eofumaric treatment, while the other treatments had similar Shannon index, Simpson’s index, and diversity index. The Z-score differential abundance between the Eofumaric and the control indicated that the inclusion of the Eofumaric treatment differentially increased the abundance of Patescibacteria, Synergistota, Chloroflexi, Actinobacteriota, Firmicutes, and Euryarchaeota while Verrucomicrobiota, WPS-2, Fibrobacterota, and Spirochaetota were decreased. The Random Forest Classification showed that the lower relative abundance of Fibrobacterota, Spirochaetota, and Elusimicrobiota and the higher relative abundance of Firmicutes and Chloroflexi were most impactful in explaining the microbial community data. Overall, the essential oil blend showed great potential as a methane gas mitigation strategy by modifying rumen fermentation through changes in the microbial community dynamics.